ANALISIS KUALITAS PELAYANAN DALAM PELAKSANAAN TERA DAN TERA ULANG ALAT UKUR, TIMBANG, TAKAR DAN PERLENGKAPANNYA (UTTP) PADA BIDANG PERDAGANGAN DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN PACITAN - Susi Minarsih; Ary Sutrischastini (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2016)
The aims of this study are to measure the level of service quality and how to improve the quality of service execution in re-measurement tera and tera of UTTP in Commerce On duty Co-Operation, Industrial and Commerce Of Sub-Province of Pacitan. This research’s object is traditional market of Minulyo Pacitan as mains market in Sub-Province of Pacitan with 100 perpetrator people of sample as user/owner of UTTP (ukur,timbang, takar, dan perlengkapannya) with method intake of sampel by Convenience Sampling. The technique of collecting data uses questionnaires and direct interview. This research use qualitative analysis instrument test of validity and reliability to know valid or not and reliabel or not about the questions of questionnaire. Then, this research was done with Servqual method as instrument to do measurement of service quality. The measurement of service quality in Servqual method pursuant to five service dimension that is tangibles, responsiveness, realibility, assurance, and empathy. This research will be measured of gap 5 that is difference among performance and its expectation. Ad for yielded gap from a enumeration of Servqual 5 gap, -146 progressively lower him mount the quality of given service activities. Therefore, its needs the existence of priority repair of service quality, in this case is service of remeasurement tera and tera of UTTP at biggest difference or gap that is at variable of Responsiveness ( Energy Listen carefully) and attribute that has smallest difference that is – 0.44 at dimension question of variable of Tangibles ( Evidence Physical).